1998
DOI: 10.1007/pl00005242
|View full text |Cite
|
Sign up to set email alerts
|

A novel Na+/Ca2+ channel blocker, NS-7, suppresses hypoxic injury in rat cerebrocortical slices

Abstract: The substance 4-(4-fluorophenyl)-2-methyl-6-(5-piperidinopentyloxy) pyrimidine hydrochloride (NS-7) has been developed recently as a cerebroprotective compound with Na+ and Ca2+ channel blocking action. In the present study, the effect of NS-7 in an in vitro model of hypoxic injury was examined and the possible involvement of Na+ and Ca2+ channels in the hypoxic injury subsequently determined. When slices of rat cerebral cortex were exposed to hypoxia/glucose deprivation followed by reoxygenation and restorati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…NS‐7 [4‐(4‐fluorophenyl)‐2‐methyl‐6‐(5‐piperidinopentyloxy) pyrimidine hydrochloride] is a newly‐synthesized neuroprotective agent. Previous in vivo and in vitro studies in cerebral cortex have shown that NS‐7 attenuated hypoxia‐induced degradation of cytoskeletal protein fodrin ( Takagaki et al ., 1997 ) and cell injury ( Tatsumi et al ., 1998b ) at 10–30 μ M , and the cellular mechanisms of NS‐7 for neuroprotection are postulated to be attributed to the blockade of voltage‐dependent Na + and Ca 2+ channels. In brain, NS‐7 bound with a K i value of 1 μ M ( Shimidzu et al ., 1997 ) to the toxin binding site 2 of the Na + channel α‐subunit, a major subunit forming the ion‐pore and the toxin binding sites 1–5 ( Catterall, 1992 ); NS‐7 at 10–30 μ M diminished the overflow of glutamate ( Shimidzu et al ., 1997 ) and dopamine ( Itoh et al ., 1998 ) caused by veratridine, a toxin that interacts with the site 2 in the transmembrane segment 6 of domain I (IS6) of the Na + channel α‐subunit ( Trainer et al ., 1996 ) and activates Na + channels ( Catterall, 1992 ).…”
Section: Introductionmentioning
confidence: 99%
“…NS‐7 [4‐(4‐fluorophenyl)‐2‐methyl‐6‐(5‐piperidinopentyloxy) pyrimidine hydrochloride] is a newly‐synthesized neuroprotective agent. Previous in vivo and in vitro studies in cerebral cortex have shown that NS‐7 attenuated hypoxia‐induced degradation of cytoskeletal protein fodrin ( Takagaki et al ., 1997 ) and cell injury ( Tatsumi et al ., 1998b ) at 10–30 μ M , and the cellular mechanisms of NS‐7 for neuroprotection are postulated to be attributed to the blockade of voltage‐dependent Na + and Ca 2+ channels. In brain, NS‐7 bound with a K i value of 1 μ M ( Shimidzu et al ., 1997 ) to the toxin binding site 2 of the Na + channel α‐subunit, a major subunit forming the ion‐pore and the toxin binding sites 1–5 ( Catterall, 1992 ); NS‐7 at 10–30 μ M diminished the overflow of glutamate ( Shimidzu et al ., 1997 ) and dopamine ( Itoh et al ., 1998 ) caused by veratridine, a toxin that interacts with the site 2 in the transmembrane segment 6 of domain I (IS6) of the Na + channel α‐subunit ( Trainer et al ., 1996 ) and activates Na + channels ( Catterall, 1992 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, intracerebroventricular injection of ω‐Aga reduces the size of cerebral infarction caused by a transient middle cerebral artery occlusion in rats (Asakura et al, 1997). More recently, we have found that the tissue injury induced in rat cerebrocortical slices by a transient exposure to hypoxia and glucose deprivation is significantly inhibited by a combined treatment with ω‐Aga and ω‐CTX (Tatsumi et al, 1998 b ). NS‐7 (3‐30 μ M ) has a cerebroprotective action in this model of hypoxic injury (Tatsumi et al, 1998 b ).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, we have found that the tissue injury induced in rat cerebrocortical slices by a transient exposure to hypoxia and glucose deprivation is significantly inhibited by a combined treatment with ω‐Aga and ω‐CTX (Tatsumi et al, 1998 b ). NS‐7 (3‐30 μ M ) has a cerebroprotective action in this model of hypoxic injury (Tatsumi et al, 1998 b ). Therefore, the blockade of the P/Q‐type Ca 2+ channel observed in the present study may contribute at least in part to the cerebroprotective action of NS‐7.…”
Section: Discussionmentioning
confidence: 99%